32.2k views
0 votes
How do you do this?? could you kindly include your work pls..

How do you do this?? could you kindly include your work pls..-example-1
User KaFu
by
5.6k points

1 Answer

5 votes

Answer:

B. 0.

Explanation:

(x + 2y)dy/dx = 2x - y

dy/dx = (2x -y)/(x + 2y)

Using implicit differentiation and the Quotient Rule:

d^2y/dx^2 = (x + 2y)(2 - y*dy/dx) - ((2x - y)(1 + 2y*dy/dx)) / (x + 2y)^2

At the point (3, 0), dy/dx = (6-0)/(3 + 2(0)) = 2.

So substituting in d^2y/dx^2, we have:

(3 + 0)(2 - 0) - (6-0)(1 + 2(0))/ (3+0)^2

= (6 - 6) / 9

= 0.

User Naou
by
4.8k points